Mangrove Forest Restoration in the Western Part of Rambut Island Wildlife Reserve, Seribu Islands - Kusmana, Cecep; Riyadi, Riffan; Suheri, Asep (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
The restoration of mangrove forests is a crucial endeavor to restore damaged areas. The area that needs restoration is the mangrove forest located in Rambut Island Wildlife Reserve. This particular mangrove forest spans approximately 14.31 hectares, with a research site covering 2.14 hectares in the western part of Rambut Island. The objectives were to accurately map the mangrove forests’s location and size that require restoration, identify mangrove species, and determine suitable restoration techniques. Sentinel-2A imagery data and field surveys conducted from July to August 2022 mapped the forest area and collected primary data on vegetation, soil, inundation, and water salinity. Based on the findings, it has been determined that approximately 0.37 hectares of the area require restoration measures. The recommended mangrove species for restoration consist of Avicennia sp., Bruguiera sp., Rhizophora sp., Ceriops sp., Heritiera sp., Sonneratia sp., and Xylocarpus sp. The planting technique that can be applied to all restoration plots, except for plot number 7, is the cemplongan technique, while the Bronjong technique is recommended for plot number 7.